2018
DOI: 10.17559/tv-20180622060024
|View full text |Cite
|
Sign up to set email alerts
|

Robust Optimization Design of Bolt-Shotcrete Support Structure in Tunnel

Abstract: The uncertainty of rock and soil parameters is one of the key problems to limit the stability of tunnel support structure. Based on this, a robust optimization design method is proposed to reduce the sensitivity of support system to the uncertainty of rock and soil parameters. By defining the design parameters, noise factors and system response, a robust design system for bolt-shotcrete support structure is established. The non-dominant solutions of system robustness and support cost consist of the Pareto Fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…First, the performance parameters of geotechnical materials possess great uncertainty, which significantly impacts the related mechanical analysis. Secondly, Wang et al [13] also showed that there will still be uncertainties in the dimensions and material performance parameters of the tunnel lining. In addition, the uncertainty of the random acts of environmental variables is also a potential threat to the structural safety of the tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…First, the performance parameters of geotechnical materials possess great uncertainty, which significantly impacts the related mechanical analysis. Secondly, Wang et al [13] also showed that there will still be uncertainties in the dimensions and material performance parameters of the tunnel lining. In addition, the uncertainty of the random acts of environmental variables is also a potential threat to the structural safety of the tunnel.…”
Section: Introductionmentioning
confidence: 99%